2016
DOI: 10.1002/zaac.201600021
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Oxygen Modulated Luminescence of an Octahedro‐hexamolybdenum Iodide Cluster having Six Apical Thiocyanate Ligands

Abstract: The synthesis, characterization, and luminescence properties of (Bu4N)2[Mo6I8(NCS)6] are reported. Orange crystals of (Bu4N)2[Mo6I8(NCS)6] were crystallized from acetone solution and used for X‐ray single‐crystal structure determination and refinement, yielding a structure with a centrosymmetric [Mo6I8(NCS)6]2– ion. Photoluminescence studies on the crystalline solid revealed a broad excitation in the UV/Vis region and an emission around 690 nm. The red emission intensity decreases with increasing partial press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 33 publications
4
30
0
Order By: Relevance
“…The advantage of using (Bu 4 N) 2 [{Mo 6 I 8 }(NO 3 ) 6 ] as precursor in ligand‐substitution reactions is based on the well known lability of coordinated nitrate, which constitutes driving force for ligand substitution. (Bu 4 N) 2 [{Mo 6 I 8 }(NO 3 ) 6 ] was also used to prepare (Bu 4 N) 2 [Mo 6 I 8 (NCS) 6 ] by reaction with KNCS, and (Bu 4 N) 2 [{Mo 6 I 8 }Cl 6 ] (orange) by reaction with HCl in CHCl 3 . Due to the presence of the H + /Cl – /NO 3 – combination, oxidation to dark‐green (Bu 4 N)[{Mo 6 I 8 }Cl 6 ] may occur during the synthesis.…”
Section: Octahedral Clusters: Chemistrymentioning
confidence: 99%
“…The advantage of using (Bu 4 N) 2 [{Mo 6 I 8 }(NO 3 ) 6 ] as precursor in ligand‐substitution reactions is based on the well known lability of coordinated nitrate, which constitutes driving force for ligand substitution. (Bu 4 N) 2 [{Mo 6 I 8 }(NO 3 ) 6 ] was also used to prepare (Bu 4 N) 2 [Mo 6 I 8 (NCS) 6 ] by reaction with KNCS, and (Bu 4 N) 2 [{Mo 6 I 8 }Cl 6 ] (orange) by reaction with HCl in CHCl 3 . Due to the presence of the H + /Cl – /NO 3 – combination, oxidation to dark‐green (Bu 4 N)[{Mo 6 I 8 }Cl 6 ] may occur during the synthesis.…”
Section: Octahedral Clusters: Chemistrymentioning
confidence: 99%
“…Exchange reactions of cations (Cs + for nBu 4 N + ) and the six apical ligands (Br -for CF 3 COO -and C 7 H 7 SO 3 -) are routine procedures that have been described elsewhere. [19][20][21][25][26] Hence, the reaction was carried out following standard procedures (see Experimental Section) until products were recrystallized from pentane/DCM to yield yellow crystalline powders containing single crystals. Single crystals were selected for an X-ray diffraction measurement with a Bruker APEX II CCD and a Bruker APEX diffractometer equipped with Mo-K α radiation (λ = 0.71073 Å) and a graphite monochromator.…”
Section: Articlementioning
confidence: 99%
“…[20,21] Comprehensive studies on molybdenum clusters have shown that the blue shift tends to increase with the electron withdrawing capability, i.e. decreasing pK s value, of the ligand.…”
Section: Solid-state Luminescencementioning
confidence: 99%
See 1 more Smart Citation
“…A strong emission quenching is observed for aerated solutions: τ em and Φ em in aerated acetonitrile solution 1 are 5.2 and 0.01 μs, respectively. Such efficient quenching of the excited states of various phosphorescent Mo 6 cluster complexes by dioxygen has been reported …”
Section: Resultsmentioning
confidence: 85%